Chromosome numbers and karyotypes of South American species and populations of Hypochaeris (Asteraceae) - Weiss-Schneeweiss, Hanna (2007)
One hundred and thirty-seven new chromosome counts are reported from 104 populations of 26 native South American taxa of Hypochaeris (Asteraceae, Lactuceae), together with two invasive Mediterranean species: H. glabra and H. radicata. First reports are provided for seven taxa (H. alba, H. cf. eremophila, H. caespitosa, H. hookeri, H. parodii, H. patagonica and H. pinnatifida) and one new ploidy level is reported (diploid for H. incana, so far known only as a tetraploid). Including the results of this study, the chromosomes of 39 of the c. 50 Hypochaeris species known from the New World have now been counted. Most species are diploid with 2n = 2x = 8 and have bimodal, asymmetrical karyotypes. Tetraploidy (2n = 4x = 16) is reported here for the first time in H. caespitosa. Infra-specific polyploidy (probably autopolyploidy) is reported in H. incana and H. taraxacoides, both cases including infra-populational cytotype mixtures (2x and 4x). Polyploidy is now known from eight South American Hypochaeris species (c. 16%). Basic karyotype analyses allow the placement of the newly counted taxa into previously proposed but slightly modified groupings and provide the framework for further molecular cytogenetic analyses. The reported findings suggest that chromosomal change in South American Hypochaeris, in contrast to Old World species, has not involved aneuploidy, but polyploidy and/or more subtle changes in chromosome length, perhaps via satellite DNA amplification/deletion or activity of retroelements, and rDNA reorganization.